State-run social protection scheme: 60pc beneficiaries not poor - The New Age (The New Age, 2014)
BRAC Institute of Governance and Development (BIGD), in association with Effective States and Inclusive Development (EISD), International Growth Centre and Think Tank Initiative, organised the three-day international conference on the political economy, accountability and governance.